SUBSTANTIATION OF THE FREQUENCY OF GRAINS COLLISIONS IN A FLOW MOVING IN A GRAVITATIONAL INSTALLATION - Arendarenko, V. M.; Samoilenko, T. V.; Antonets, A. V.; Ivanov, O. M.; Yaprynets, T. S.; Flegantov, L. O. (Scientific Progress & Innovations, 2022)
The article presents theoretical studies of the dynamics of the particles collision in a bulk grain flow moving in a gravitational installation. It is known that falling grain from a height on the concrete bottom of silos is injured. A peripheral open helical channel is available to reduce or eliminate injury. During the movement of the grains in the helical channel, they may rub or collide and be damaged. The movement of individual grains of wheat on the working surface of the helical channel is under the action of gravity. The grains are constantly in contact with each other, such interaction is characterized by a flat oblique-central impact. When considering the process of collision of two grains, the following assumption is made: the impact grains have perfectly smooth surfaces. Accordingly, according to Gauss's hypothesis, there is a connection between tangential and normal impulses, which makes it possible to determine the rate of fluctuation of grains when they collide. The Ackermann-Schen’s method was used to determine the frequency of wheat grains collisions of bulk grain material. According to the above method, the average frequency of grains collisions in the bulk grain flow with their oblique-central impact depends on the angle of inclination of the screw gravity unit acceleration section. The dependence for determining the rate of grains fluctuation in their collision is obtained. The formula for determining the average frequency of grains collisions in the bulk grain flow with their obliquely central impact on the overclocking section of the installation is given. The mathematical model obtained as a result of research characterizes the average frequency of grains collisions of loose grain flow moving along the accelerating section of the peripheral open helical channel (POHC). The analytical model can be used in the design and installation POHC in the silo.